Study of Stroke Incidence in the Aseer Region, Southwestern Saudi Arabia - Adel A. Alhazzani (International Journal of Environmental Research and Public Health, 2018)
Recent data regarding first-stroke incidence in Saudi Arabia in general and in the Aseer region in particular are scarce and even lacking. The aim of this work was to study the first-time stroke incidence in the Aseer region, southwestern Saudi Arabia. All first-stroke patients admitted to all hospitals in the Aseer region over a one-year period (January through December 2016) were included. Stroke patients outside the Aseer region were excluded from the study. The incidence per 100,000 patients and the concomitant 95% CI (Confidence Intervals) were computed. The present study included 1249 first-time stroke patients and calculated an overall minimal incidence rate of hospitalized first-time stroke of 57.64 per 100,000 persons per year (95% CI: 57.57–57.70). A steady increase was noticed depending on the patients' age, reaching a figure of 851.81 (95% CI: 849.2–854.5) for those patients aged 70 years and more. Overall, the incidence rate for females (48.14; 95% CI: 48.04–48.24) was lower compared to males (65.52; 95% CI: 65.1–66.0). Taking into consideration the expected rise of the elderly because of the prominent medical services provided by the Saudi government, leading to a subsequent change in the horizontal and vertical age distribution structure of the population, an increase in the number of stroke patients is expected. It is suggested to establish a nationwide stroke surveillance system in the Kingdom, with the objective to report, analyze, and maintain an updated overview of the stroke status in Saudi Arabia.